2002
DOI: 10.1002/14651858.cd001773
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis

Abstract: Non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
1
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 52 publications
0
60
1
26
Order By: Relevance
“…A recent Cochrane Database systematic literature review on non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis concluded that in the absence of randomized controlled studies it is impossible to set definitive rules for treatment (21). In case of intractable haemorrhage arterial embolization or ligation and/or cystectomy represent definitive treatment, at the cost of increased morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane Database systematic literature review on non-surgical interventions for late radiation cystitis in patients who have received radical radiotherapy to the pelvis concluded that in the absence of randomized controlled studies it is impossible to set definitive rules for treatment (21). In case of intractable haemorrhage arterial embolization or ligation and/or cystectomy represent definitive treatment, at the cost of increased morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…This usually occurs during the treatment period, and involves an acute inflammatory response and tissue edema. 4 The underlying pathology of late adverse effects is different from that seen in the acute reaction. Late-responding tissues, such as vascular and connective tissues, have a slow turnover rate; therefore, while they sustain radiation damage at the time of treatment, the effects are not expressed until repeated cell division is attempted.…”
Section: Pathologymentioning
confidence: 99%
“…Late-responding tissues, such as vascular and connective tissues, have a slow turnover rate; therefore, while they sustain radiation damage at the time of treatment, the effects are not expressed until repeated cell division is attempted. 4 For this reason, late radiation tissue injury can take several months to many years to develop, and is largely a function of the total radiation dose and fraction size. The pathological hallmark of late radiation tissue injury is obliterative endarteritis resulting in atrophy and fibrosis.…”
Section: Pathologymentioning
confidence: 99%
“…Most available data about radiation cystitis treatment come from a small number of descriptive studies or from expert opinions [2,4]. As clinical data are considered to have low quality then physicians, who are still facing patients with a disease hugely influencing quality of life, mostly base on their own experience.…”
Section: Introductionmentioning
confidence: 99%